2015
DOI: 10.1080/15548627.2015.1055439
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP3 promotes survival of CD4 T cells by restricting MTOR and promoting autophagy

Abstract: Autophagy plays important roles in metabolism, differentiation, and survival in T cells. TNFAIP3/A20 is a ubiquitin-editing enzyme that is thought to be a negative regulator of autophagy in cell lines. However, the role of TNFAIP3 in autophagy remains unclear. To determine whether TNFAIP3 regulates autophagy in CD4 T cells, we first analyzed Tnfaip3-deficient naïve CD4 T cells in vitro. We demonstrated that Tnfaip3-deficient CD4 T cells exhibited reduced MAP1LC3/LC3 (microtubule-associated protein 1 light chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 42 publications
(61 reference statements)
4
81
1
Order By: Relevance
“…Our recent studies have shown that RIPK, a key molecule of necroptosis, can regulate autophagy through the regulation of p62-LC3 complex formation [63]. Also, the ubiquitin-editing enzyme A20 appears to promote autophagy through its complex formation with MTOR, and regulate the survival in CD4 T-cells [64]. Further studies focusing on the molecular interactions linking autophagy, necroptosis, and ER stress may provide new insights to the pathophysiology of Paneth cell-driven ileal CD.…”
Section: Role Of Iecs In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…Our recent studies have shown that RIPK, a key molecule of necroptosis, can regulate autophagy through the regulation of p62-LC3 complex formation [63]. Also, the ubiquitin-editing enzyme A20 appears to promote autophagy through its complex formation with MTOR, and regulate the survival in CD4 T-cells [64]. Further studies focusing on the molecular interactions linking autophagy, necroptosis, and ER stress may provide new insights to the pathophysiology of Paneth cell-driven ileal CD.…”
Section: Role Of Iecs In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…Indeed, our single-round infection using VSV-Gpseudotyped HIV revealed restriction mechanisms acting during reverse transcription and prior to integration. Moreover, mTOR is a well-established regulator of autophagy (79,82), a process that may be involved in the degradation of the incoming HIV upon fusion/uncoating (83,84). By promoting the mTOR activity, ATRA may impair the autophagy process in CCR5 + CCR6…”
Section: On Hiv Replication In Ccr6mentioning
confidence: 99%
“…7C, D ), suggesting that A20 activation is important but not suffi cient, and full inhibition of NLRP3 infl ammasome necessitates the coordinated involvement of additional factors. One of these factors may be autophagy because Matsuzawa et al ( 40 ) reported that A20 activation and autophagy cooperate in T-cell survival.…”
Section: Inhibition Of A20 and Ampk Activation Altered Il-1 ␤ Secretimentioning
confidence: 99%